KAJIAN PENGARUH PENINGKATAN KONSENTRASI EKSTRAK KHAMIR PADA MEDIA HESTRIN DAN SCHRAMM TERHADAP PEROLEHAN SELULOSA OLEH Acetobacter liquefaciens SRC-4 - Ermina Sari (Universitas Lancang Kuning, 2016)
SRC-4 starin is one of bacteria sellulose producing strains. It was obtained from the rotten coconut meat from Semplak, Bogor. The objective of this study is to obtain the optimum composition of modified HS medium to produce cellulose, by increasing yeast extract concentration and also combination of carbon and vitamin sources. The production of cellulose by SRC-4 was done by 18 treatments on static culture. The increasing of yeast extract concentration, combination of carbon and vitamin sources gave significant effect to the production of cellulose. The highest yield of cellulose was produced at the treatment consist of 1.0 % yeat extract (as nitrogen source), 1 % glucose + 1 % glycerol (as carbon source) and 0.164 ppm vitamin B1 + 0.020 ppm vitamin B2 (as vitamin source). Kata Kunci: cellulose, Acetobacter liquefaciens SRC-4, yeast